Spermine driven water deficit tolerance in early growth phases of sweet corn genotypes under hydroponic cultivation - Tahoora Batool Zargar; Mawia Sobh; Oqba Basal; Tibor Janda; Magda Pál; Szilvia Veres (Scientific Reports)
Abstract Sweet corn is highly susceptible to water deprivation, making it crucial to identify effective strategies for enhancing its tolerance to water deficit conditions. This study investigates the novel application of Spermine as a bio-stimulant to improve sweet corn (Zea mays L. var. saccharata) resilience under hydroponic water deficit conditions. Four genotypes (Dessert, Messenger, Tyson, and Royalty) were treated with Spermine (0.2 mM foliar application), polyethylene glycol 6000 (8% and 12%), and their combinations. The impacts on growth parameters, photosynthetic performance, and oxidative stress markers were evaluated. Spermine significantly enhanced biomass parameters, counteracting the severe reductions caused by PEG-induced water deprivation. In the Dessert and Tyson genotypes, total biomass increased by 145%, while it increased by 118% in Messenger and 110% in Royalty when treated with Spermine under severe water deprivation. However, Spermine treatment application did not recorded higher differences compared to control under non water deficit conditions. In the Dessert genotype, root length increased by 36.6% under combined treatment compared to 12% PEG alone. Spermine also mitigated reductions in shoot length, improved by 90.6% and specific leaf area, with a notable 272.6% increase in Tyson under severe water deficit. Photosynthetic performance, including chlorophyll and carotenoid levels, was enhanced, with a 103.1% increase in relative chlorophyll content in Dessert under severe water deprivation. Spermine also reduced oxidative damage, as indicated by a 48.7% decrease in malondialdehyde levels in Tyson, and increased peroxidase activity, enhancing antioxidant defense in Messenger under severe water deprivation. The quantum efficiency of Photosystem II, which was significantly reduced by water deficit, showed substantial improvement with Spermine treatment, with increases of 107.2% in Tyson and 99.4% in Royalty under moderate water deprivation. These results highlight the potential of Spermine as an effective strategy to improve sweet corn resilience under water-limited conditions, offering a novel approach for sustainable crop management.